1978
DOI: 10.1111/j.1365-2621.1978.tb02331.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Hydroxyproline Solubilized to Tenderness of Bovine Muscle

Abstract: Hydroxyproline assay and sensory evaluation were used to study tenderizing effects of two oven temperatures (94", 149°C) and two endpoint temperatures (70", 80°C) on top round steaks cooked in oven film bags. Hydroxyproline solubilized during cooking ranged from 1.47-1.80%, and did not differ significantly between oven temperatures or between end-point temperatures. Sensory tenderness scores were higher (P < 0.01) for steaks cooked to 70" than for steaks cooked to 80°C. With cooking at 94-80°C hydroxyproline s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
1

Year Published

1981
1981
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
2
8
1
Order By: Relevance
“…No positive correlation between collagen solubility and shear force measurements was observed. These results disagree with Herring et al (1967), Field et al (1970), Bailey (1972) and Williams and Harrison (1978) who reported a positive correlation between collagen solubility and tenderness.…”
Section: Toughness Studies Bycontrasting
confidence: 93%
“…No positive correlation between collagen solubility and shear force measurements was observed. These results disagree with Herring et al (1967), Field et al (1970), Bailey (1972) and Williams and Harrison (1978) who reported a positive correlation between collagen solubility and tenderness.…”
Section: Toughness Studies Bycontrasting
confidence: 93%
“…Hydroxyproline solubilization was not affected by endpoint temperature at either heating rate (Table 2). This is in agreement with the work of Williams and Harrison (1978) but is in contrast to the findings of Paul et al (1973) and Penfield and Meyer (1975) who reported increased hydroxyproline solubilization with increased endpoint temperature.…”
Section: Hydroxyproline Solubilizationsupporting
confidence: 91%
“…A final internal temperature of 68°C was attained to correspond with the final temperature of the roasts used for sensory evaluation. This dry cooking procedure was based on the method suggested by Williams and Harrison (1978) for the assessment of correlations between collagen determination, shear force measurements and tenderness of expensive cuts of meat. Cooked samples were cooled under cold running water.…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Uytterhaegen et al (1994) have reported increased toughness in meat from DM Belgian Blue that was due to their reduced postmortem proteolytic tenderization in comparison with normal Belgian Blue. It must be mentioned that the dry cooking procedure (Williams and Harrison 1978) yields smaller amounts of soluble collagen than the salt, acid or alkali solution extraction procedures (Light 1985). This procedure, on the other hand, has potential to favour the establishment of relationship with shear forces.…”
Section: Breed Of Sire × Dam Combinationmentioning
confidence: 99%